Filtering tricks for FSK demodulation. - Shiung, D. (IEEE Signal processing magazine)
In this article, we present a useful trick to make the implementation of a digital noncoherent frequency shift keying (FSK) demodulator more economical from a hardware complexity standpoint, with the goal of minimizing its computational workload. The article also utilizes comb filters in removing the dc offset from the signals and in reducing the complexity of follow-on filtering. The corrected signal is amenable to additional processing at the IF frequency or may be down-converted to a baseband frequency for further processing.